Handbook of Healthcare Delivery Systems. - Yih, Yuehwern (Industrial and systems engineering series., 2010)
With rapidly rising healthcare costs directly impacting the economy and quality of life, resolving improvement challenges in areas such as safety, effectiveness, patient-centeredness, timeliness, efficiency, and equity has become paramount. Using a system engineering perspective, Handbook of Healthcare Delivery Systems offers theoretical foundations, methodologies, and case studies in each main sector of the system. It explores how system engineering methodologies and their applications in designing, evaluating, and optimizing the operations of the healthcare system could improve patient outco.